Parasitic otitis caused by Rhabditis (Rhabditis) freitasi (Nematoda: Rhabditidae) in the cattle Gir breed in the State of Acre - Monteiro E Silva, Francirley; De Araújo Santos, Francisco Glauco; Montoya-Flórez, Luis Mauricio [UNESP]; Rocha, Noeme Sousa [UNESP]; Diniz, Jefferson Viana Alves (My University, 2016)
The bovine parasitic otitis has been reported in several states of Brazil. It is caused by rhabditiforms nematodes, attacking cattle Gir and Indubrasil breeds. The aim of this work was to describe the occurrence of the disease in animals of the cattle Gir breed in Rio Branco, State of Acre, Brazil. The animals belonged to the Station of Improvement and Animal Genetic Diffusion. Samples were collected from five of these individuals, with swabs aid, conditioned in plastic tubes and kept in alcohol 70%. The specimens were visualized using optical microscopy, and the morphometry was accomplished through a micrometrical ocular. The data were inserted in the Excel spreadsheet, running on Windows 7, and analyzed through descriptive statistics. The animals presented purulent secretion in the external ear canals, shook their heads, showed inquietude and sensibility to the touch during the clinical trials, when intense infestation was observed. One of the individuals died. Animal genetic improvement programs are negatively interfered by infestations like these. It was possible and opportune to find out the moment and place how such illness has entered in the state of Acre. This work aims to help reinforce the importance of future studies to report new cases in the state of Acre.
Keywords: Cattle; Gir breed; Parasitic otitis; Rhabditis sp.